How the Private Sector Can Benefit from Being Part of CCAFS - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Mamadou Khouma from IDEV-Senegal (Private Sector). Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya